Ishmael : An adventure of the mind and spirit - Quinn, Daniel (New York Bantam/turner book, 1992)
Ishmael is an utterly unique and captivating spiritual adventure which redefines what it is to be human. We are introduced to Ishmael, a creature of immense wisdom. He has a story to tell, one that no human being has ever heard before. It is the story of man's place in the grand scheme, and it begins at the birth of time. This history of the world has never appeared in any schoolbook. "Does the earth belong to man?" Ishmael asks. "Or does man belong to the earth?"
Keywords: Tham khảo